Sustainable Development of Tourism in Historical Maramures Case Study: Breb Village - Berlingher, Vasile (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2014)
Sustainable development has become an extremely important issue for both the academic as well as the economic and political sectors during recent years. The concept of sustainable development has emerged in the context of the announced danger of planet and surrounding environment destruction as a result of the investments made in all areas of activity throughout the world. One of the concept objectives is to find a solution to reconcile three desiderata: economic growth, environmental quality and social justice. The specialists have introduced this concept in order to make investments and to create business environments able to bring about an economic growth in a strong connection with nature, without destroying the natural resources. Tourism comes from behind with a tremendous force, a new economic market orientation strongly connected to nature. It provides us with the opportunity to review the main challenges faced during recent years in relation to the environmental, cultural and interpersonal relationships, in order to develop, protect and preserve the touristic potential. The historical Maramures represents such a region with a strong touristic potential. A study performed by Pricewaterhouse Coopers Management Consultants on the attractiveness of Romania‟s development regions places it on the II-nd position and illustrates the capacity of the region to develop and attract investments able to support the sustainable development of the area without destroying its uniqueness and originality. The herein study focusses on one of the Maramures villages that has managed to fully retain its originality and cultural uniqueness through the wooden houses, the Maramures traditional gates, the local traditional vestments and the ancient customs. Foreign investors have come into this village to set up traditional accommodation facilities, true to the style of the area, to restore old wooden houses, thus becoming sometimes more fond of the area than the population itself. It is interesting to notice how these investors move out from the big capitals into a mountain village and struggle to preserve the strong tourism potential in the area, while local residents want to leave this community towards the big metropolis. The study presents the touristic potential of Breb Village as well as several projects for sustainable development of tourism in this mountain hamlet. Some of these projects are still undergoing, others are already completed. All are run by foreign investors who undertake actions in order to make the local population aware of the importance of preserving the natural environment and cultural heritage of this area.